Pelviureteric junction obstruction in ectopic kidneys with extrarenal calyces: A rare renal anomaly - Ravi Prakash Kanojia; Karmon Janssen; Andrew Kirsch (Wolters Kluwer Medknow Publications, 2021)
Extrarenal calyces (ERC) is a rare renal anomaly where calyces lie outside the renal parenchyma and are connected to pelvis by draining infundibulum. Its presentation with pelviureteric junction obstruction presents a confusing intraoperative finding. We report two cases of ERC with pelviureteric junction obstruction in the ectopic kidney. Emphasis is laid on the defining the anatomy so that reader can identify the condition if he comes across similar situation. The two patients were managed by minimal access approach. Management of these cases and review of pediatric cases reported in literature are discussed.